The association of oral health knowledge with the behavior of pregnant women visiting the dentist based on the theory of planned behavior: Cross-sectional studies - Rizqi, Dikkara; Suryanti, Netty; Suwargiani, Anne Agustina; Andiesta, Niekla Survia (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: A lack of knowledge of oral health maintenance among pregnant women affects the behavior of maintaining poor oral health.  It is important for pregnant women to visit the dentist due to their increased susceptibility to oral diseases, which can adversely impact pregnancy outcomes, including premature birth and low birth weight. According to the theory of planned behavior, a mother's knowledge can influence her health-related behavior. To determine the level of oral health knowledge among pregnant women and to examine the relationship between this knowledge and the factors that influence their behavior regarding dental visits. Methods: This study uses a correlational analytical design with a cross-sectional approach, focusing on pregnant women at the Cijerah Community Health Centerin Bandung City, Indonesia. A purposive sampling method resulted 67 participants. A new questionnaire assessed oral health knowledge (20 items) and factors influencinh visiting behavior based on the theory of planned behavior (26 items). Data analysis used the Spearman correlation test. Results:Most pregnant women (76.2%) had insufficient oral health knowledge, but showed a positive attitude towards dental visits in the first trimester and every six months (11.91 ± 2.66 and 11.65 ± 2.87). They also reported good subjective norm (28.73 ± 5.42 and 28.31 ± 5.19), good behavioral control (8.23 ± 1.67 and 8.32 ± 1.61) and good intention (3.94 ± 0.96 and 3.83 ± 1.06). Conclusion: The level of oral health knowledge is  low, and althoughfactors influencing the dental visit behavior are positive, there is no correlation between this knowledge and factors that influence the behavior of visiting the dentist.